CT Brain Prescriptions in Talairach Space: A New Clinical Standard - Weiss, Kenneth L.; Storrs, Judd; Weiss, Jane L.; Strub, William (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Head CT prescriptions are currently plagued by intra- and intersubject image variance and do not match standardized MR imaging planes. We developed and tested a simple method to improve CT precision and approximate the Talairach reference standard advocated for MR imaging.METHODS: We retrospectively reviewed midline sagittal T2-weighted brain MR images of 126 consecutive patients to determine the mean angle subtended by the Talairach anterior commissure-posterior commissure (AC-PC) line and the hard palate. On the basis of this data set, a new head CT protocol was instituted with pitch similarly prescribed relative to the hard palate as identified on the lateral CT scout film. We then compared the precision of the new protocol, our former method (nominally parallel to the orbito-meatal line) and fixed-gantry angulation. Two head CT studies from 50 consecutive patients imaged with our old protocol and 50 consecutive patients imaged with our new protocol were reviewed for a total of 200 CT examinations.RESULTS: The Talairach AC-PC line was rotated 12.0° ± 6.1° from the hard palate line and 15.6° ± 10.1° from the axial plane of the magnet. The new CT protocol approximated the Talairach-referenced MR images obtained at our institution and improved intrapatient CT scan precision compared with fixed-gantry selection (P < .004) and compared with our previous prescription technique (P < .064; P < .025, controlling for excessive head extension).CONCLUSION: By prescribing CT images angled +12° from the hard palate, a structure readily identified by technologists, interscan precision can be improved and Talairach-referenced MR imaging studies can be approximated. Along with AC-PC-referenced MR imaging studies, we advocate this CT protocol as a new clinical standard.